PEMODELAN REGRESI LOGISTIK PADA FAKTOR FISIK DAN KELELAHAN KERJA DENGAN RISIKO KERJA PEKERJA PROYEK PEMBANGUNAN JALAN TOL MEDAN – BINJAI DI PT. HUTAMA KARYA INFRASTRUKTUR - Novrika Silalahi; Natalia Magdalena Simbolon (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Infrastructure take hold of an important role as one of the cogs of economic growth and development in every country including Indonesia. The negative impacts arising from the process of infrastructure development / construction are the emergence of work accident rates due to the risk of unsafe work environments and unsafe actions taken by workers. This research is an analytical survey with Cross Sectional Design involving 150 employees of PT. Hutama Karya Infrastruktur as a population and uses the Slovin formula as a sample of 60 people. Data obtained by interview and using questionnaires. Analysis of the data used is univariate, bivariate using the chi-square test and mutivariate using the Multiple Logistic Regression Test with the enter method. Based on the chi square test, the results obtained variables related to work risk are dust in the work environment (p <0.017), noise (p = 0.025), work fatigue (p = 0.005). The results showed that the three variables were candidates who entered into the multivariate analysis modeling namely dust in the work environment, noise, and work fatigue. The most related or dominant analysis result is work fatigue variable (2,268). Therefore, researchers suggest that workers always apply SOP on safety to avoid the risk of work accidents.